(untitled) (The Peerian Journal, 2025)
The research aims to determine the extent of the impact of integrating block chain technology with artificial intelligence in enhancing the application of electronic auditing, and the research started from the main question of revealing the extent of the impact of using block chain technology in enhancing the application of electronic auditing, and the researcher relied in conducting their research on the descriptive and analytical approach to a number of research and studies that addressed the use of block chain technology and artificial intelligence in the financial auditing process These studies showed a low incidence of any human fraud or fraud, and the research reached a set of conclusions, the most important of which is the use of Block chain and artificial intelligence technologies gives confidence and security to customers who are subject to.